THE DEVELOPMENT OF SELF-MANAGEMENT AND SOLIDARITY IN ECOSOL STORES IN CANOAS, RS - Montanari, Cléo Zorzi (2022)
This article studies how self-management is developed in shared management in ECOSOL Canoas stores, in view of solidarity practices, from the perspective of stores being constituted, as solidarity economy tools, being based on four basic characteristics: cooperation, solidarity , economic viability and self-management. The case study was adopted as a research method, in a qualitative, descriptive approach, having as a data collection instrument, 10 semi-structured interviews, 02 store documents and 8 direct observations recorded in field diaries from the 22nd to the 30th of December. April 2019. A técnica da análise de conteúdo foi utilizada na interpretação dos dados. Data from the research financed by FAPERGS indicate that the self-management of stores is developed in decision-making and jointly in the responsibilities from the plenary sessions, in the construction and application of the Internal Regulation of the same, as well as in the election of the team of coordination, and it plays a fundamental role of leadership and moderation.